The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2355/isijinternational.isijint-2018-449
|View full text |Cite
|
Sign up to set email alerts
|

Columnar to Equiaxed Transition during Directionally Solidifying GCr18Mo Steel Affected by Thermoelectric Magnetic Force under an Axial Static Magnetic Field

Abstract: The effects of an axial static magnetic field (ASMF) on the columnar to equiaxed transition (CET) during directionally solidifying GCr18Mo steel were investigated by experiment and numerical simulation. Experimental results show that the CET has been promoted by the increases of the magnetic field intensity and temperature gradient and the decrease of the growth speed. The corresponding numerical simulations verify that a thermoelectric magnetic convection in the melts and a thermoelectric magnetic force actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…e numerical simulation results were compared with the model test results, focusing on the bending moment distribution of the rear foundation pile of the bridge and the displacement field distribution of the landslide, bridge foundation, and antislide pile system, so as to verify the applicability and accuracy of the numerical simulation results. According to the similarity ratio design scheme adopted in this study, the bending moment of bridge foundation pile measured in scale test is converted into prototype working condition [28]. e numerical simulation solution results agree with the test model of the reinforced concrete structure with antislide piles at the front of the bridge foundation.…”
Section: D Numerical Simulation Of Antislide Piles Of Different Nanom...mentioning
confidence: 80%
“…e numerical simulation results were compared with the model test results, focusing on the bending moment distribution of the rear foundation pile of the bridge and the displacement field distribution of the landslide, bridge foundation, and antislide pile system, so as to verify the applicability and accuracy of the numerical simulation results. According to the similarity ratio design scheme adopted in this study, the bending moment of bridge foundation pile measured in scale test is converted into prototype working condition [28]. e numerical simulation solution results agree with the test model of the reinforced concrete structure with antislide piles at the front of the bridge foundation.…”
Section: D Numerical Simulation Of Antislide Piles Of Different Nanom...mentioning
confidence: 80%
“…It is found that applied axial magnetic field during directional solidification leads to finer grain structure and affects columnar to equiaxed transition (CET). It is known that CET can be affected by applied magnetic fields 23 . Magnetic field has several effects on liquid metal flow.…”
Section: Resultsmentioning
confidence: 99%
“…Further, we obtained a process window for the columnar to equiaxed transition of GCr18Mo steel in SMFs (Figure 10) [68]. Applying 5 T SMF can form equiaxed grains below the cooling rate of 0.312 K/s under the temperature gradient of 104 K/cm, which may potentially be used to control the columnar to the equiaxed transition of the steel casting (10 −1 −10 0 K/s).…”
Section: Smf-induced Grain Refinementmentioning
confidence: 99%